Coir Pith – A Medium for Oil Absorption - Parameswaran, P. S.; Ravindranath, Anita Das; Sarma, U. S. (International Coconut Community, 2019)
Coir pith, the byproduct of coconut husk, due to its abundance nature and its porous structure can be effectively used for oil adsorption. Modification of coir pith to make as hydrophobic may allow them to be used for oil adsorption. Oil spills can destroy marine aquatic life and have a great impact on environment. In this study coir pith have been treated enzymatically (Lipase, Protease & Glucanase) and chemically (Acetylation) to impart hydrophobicity and to enhance oil adsorption capacity. The coir pith samples were characterized periodically by FTIR, SEM. The extent of acetylation was evaluated by weight percent gain.The results suggests that acetylated coir pith could be beneficial in oil adsorption and potentially provide a low cost environmentally friend adsorbent for oil spill.